- None: ANALISIS PENGARUH SUKUK IJARAH TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyudi; Agustiar; Ardelia; Salsabila, Musrifah (ITB AAS INDONESIA Surakarta, 2025)
The sukuk market in Indonesia has shown significant growth in recent decades. This study focuses on analyzing the effect of the Current Ratio (CR) and Sukuk to Equity Ratio (SER) on Return on Assets (ROA) in companies that issue Sukuk Ijarah. This study uses a quantitative approach and documentation method with panel data regression on 12 companies that issued sukuk ijarah during the period 2017–2024. The estimation model used is the Common Effect Model. Classical assumption tests were conducted, including multicollinearity and heteroscedasticity tests, which showed that there were no indications of multicollinearity and heteroscedasticity, so that regression analysis could be performed. The t-test results indicate that the Sukuk to Equity Ratio has no significant partial effect, while the Current Ratio has a negative and significant effect on ROA. This indicates that an increase in the Current Ratio will be followed by a decline in company profitability. However, based on the F test, both variables have a simultaneous effect on ROA. The coefficient of determination (R²) value shows that the model is able to explain 7.95% of the variation in ROA, while the rest is explained by other variables outside the model.